2019
DOI: 10.18203/2349-3291.ijcp20194746
|View full text |Cite
|
Sign up to set email alerts
|

A study on clinical profile of typhoid fever at Government General Hospital, Nizamabad, Telangana, India

Abstract: Background: The disease is most common in India. Children are most commonly affected. Typhoid fever, also known simply as typhoid, is a bacterial infection due to specific type of Salmonella that causes symptoms.Methods: Prospective observational study, 100 children with fever more than 7 days attending pediatric departed at GGH, Nizamabad were included in this study.Results: Total 100 children included in this study, male were 62, female were 38. More cases were (43) in 5-10 years age group, 53 children, belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
2
3
1
1
Order By: Relevance
“…We found that 16 cases (32%) of patient gathering had migraine. This outcome came in concurrence with [13] who revealed cerebral pain in (32%) of cases. these outcomes came interestingly with [14] who discovered cerebral pain in (58%) of their cases.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We found that 16 cases (32%) of patient gathering had migraine. This outcome came in concurrence with [13] who revealed cerebral pain in (32%) of cases. these outcomes came interestingly with [14] who discovered cerebral pain in (58%) of their cases.…”
Section: Discussionsupporting
confidence: 77%
“…These outcomes came conversely with[12] who discovered fever in (75.8%) of his cases.We found that 16 cases (32%) of patient gathering had migraine. This outcome came in concurrence with[13] who revealed cerebral pain in (32%) of cases. these outcomes came interestingly with[14] who discovered cerebral pain in (58%) of their cases.We discovered 33 cases (66%) of the patient gathering had stomach torment this outcome come in concurrence with[15] who discovered stomach torment in (68%) of patients.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Although no deaths were reported http://www.sajid.co.za Open Access during this outbreak, a high burden of typhoid fever in children is a public health concern, as there is a > 4 time's risk of mortality because of increased risk of complications and prolonged hospitalisation that has been observed in other settings. 25,26 The high burden of typhoid fever amongst children in this study specifies the high-risk population but also enables policymakers and municipal service delivery sectors to make informed decisions on prioritisation of safe water supply in schools and the community in general.…”
Section: Discussionmentioning
confidence: 99%
“…Typhoid fever is common among children aged more than 2 years old and teenagers in Malaysia (Ministry of Health Malaysia, 2017a). Other symptoms, such as headache, malaise, coughing and loss of appetite, were reported as early signs but the most common symptom for this disease is prolonged fever (Laishram and Singh, 2016;Roy et al, 2016;Ministry of Health Malaysia, 2017a;Singh and Sundar, 2019). Abdominal symptoms ranging from discomfort, pain, constipations, and diarrhea have been reported as well (Rasul et al, 2017;N'Cho et al, 2019;Muhammad et al, 2020).…”
Section: Typhoidmentioning
confidence: 99%